PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KOMUNIKASI MATEMATIS SISWA DI SDN CIBENING 01 KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Amaliyah, Pirda; Lestari, Hana; Mukri, Rusdiono; Rahmawati, Ima (Prodi PGMI IAI Sahid, 2026)
The ability to convey mathematical concepts verbally and non-verbally is known as mathematical communication. Students' mathematical communication can be improved through the ethnomathematics-based PBL model. This study aims to analyze the application of the ethnomathematics-based PBL model to enhance students' mathematical communication in mathematics subjects. The method used is a pre-experiment with a one-group pretest-posttest design. This research was conducted on fourth-grade students at SDN Cibening 01, Paamijahan District, Bogor Regency. The sample used was non-probability sampling, with a total sample in class IV, consisting of 30 students. The instruments used were students' mathematical communication tests and observation sheets to implement the ethnomathematics-based PBL model. The mathematical communication test was administered in two stages, namely pretest and posttest. The research obtained an average score of students' mathematical communication on the pretest of 50.78%, while on the posttest it was 82.07%. Data processing was analyzed using SPSS 26 for Windows with paired sample t-test with α (0.01) with a significance value of 0.000 <0.01. The results showed that there was a significant increase in students' mathematical communication between pretest and posttest. Thus, it can be concluded that there is an increase in students' mathematical communication before and after the application of the ethnomathematics-based PBL model in class IV SDN Cibening 01.